2000
DOI: 10.1021/jp003574z
|View full text |Cite
|
Sign up to set email alerts
|

Cyano, Amino, and Trifluoromethyl Substituent Effects on the Claisen Rearrangement

Abstract: Ab initio quantum mechanical methods with the B3LYP/6-31G* method were used to model the reactants, transition states, and products of Claisen rearrangements of allyl vinyl ethers substituted at all positions with CN, NH 2 or CF 3 groups. The calculations predict that 1-CN, 1-CF 3 -cis, 5-NH 2 , 6-CN, and 6-CF 3 substituents increase the activation barriers, in agreement with experimental results on substituent effects by CN, CF 3 , and the related 5-OCH 3 example. All other substituents lower activation energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 44 publications
3
29
0
Order By: Relevance
“…On the other hand, substituting EDG such as NH 2 and OCH 3 to X1 enhances the stability of the product by delocalizing a lone pair of electrons to the carbonyl π* orbital. In particular, NH 2 forms an amide bond with the carbonyl group and significantly stabilizes the product [34,35] . It is known that reaction barriers often correlate with products’ stability [36,37] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, substituting EDG such as NH 2 and OCH 3 to X1 enhances the stability of the product by delocalizing a lone pair of electrons to the carbonyl π* orbital. In particular, NH 2 forms an amide bond with the carbonyl group and significantly stabilizes the product [34,35] . It is known that reaction barriers often correlate with products’ stability [36,37] .…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the interaction between HOMO of the enolate moiety and LUMO of the allyl moiety favors the Claisen rearrangement. [34,35] More specifically, the reactivity is enhanced when HOMO's MO coefficients at C2 and LUMO's MO coefficients at C4 and C5 are high. It was also discussed that substituting EDG to X1 and EWG to X2 increase HOMO's MO coefficients at C2 and that substituting EWG to X3 and EDG to X4 and X5 increase LUMO's MO coefficients at C4 and C5.…”
Section: Chemical Analysismentioning
confidence: 99%
“…To achieve a more quantitative estimate of substituent effects on the chemoselectivity of the N-aryl-2-vinylaziridines to benzoazepines rearrangement, we have tried to correlate the activation energies of the rate-determining step, 1 to 1 I, with the corresponding reaction energies. The activation energies of Claisen rearrangements have been shown to be related to the corresponding reaction energies [62] through Marcus theory. [63] Briefly, Marcus theory allows the separation of the energy barrier into intrinsic and thermodynamic contributions [Eq.…”
Section: Mechanism Of the [33]-claisen Rearrangementmentioning
confidence: 99%
“…Cyanomethyl vinyl ethers (CMVEs) 1 constitute densely functionalized linear synthetic platforms which have found use as monomeric units in the construction of alkenyl ether-vinyl ester copolymers [ 1 , 2 , 3 , 4 , 5 ], as building blocks in the construction of multi-substituted 2,3-dihydrofurans [ 6 , 7 ] and 2,3-dihydropyrroles [ 7 ], and as convenient platforms for mechanistic investigations in the Claisen rearrangement of allyl vinyl ethers [ 8 , 9 , 10 ] ( Scheme 1 A). They are usually synthesized in a step-wise manner from the corresponding aldehydes through the formation of the O -formyl cyanohydrin intermediate and carbonyl methylenation [ 9 ] ( Scheme 1 B).…”
Section: Introductionmentioning
confidence: 99%